SAP on the cloud - Missbach, Michael (Management for Professionals, 2013)
This book provides an introduction to the various facets of building and operating an SAP infrastructure exploiting Cloud technologies. It describes and discusses the latest developments and challenges and suitable solutions, and also outlines future trends where possible. To ensure that this book is also useful to readers who do not consider themselves experts in this area, this book explains in detail the backgrounds of the various solutions. Also, practice-oriented case studies are provided throughout the book in order to make the reader aware of essential but perhaps less obvious points. However, the book concentrates exclusively on the set up and operation of the SAP infrastructure. It does not give details on how to install and customize the SAP software, nor does it deal with the much more complex tasks involved in business process implementation and reengineering.